A negação da shoah na História: uma análise dos trabalhos Negacionistas enquanto História e o problema da administração da Memória - NARCIZO, Makchwell Coimbra (2012)
The shoah (holocaust) is a remarkable event in our contemporaneity, especially by the way it was developed and for its results. The humanity faced a barbarity that never thought was possible in modern world, generating the disarticulation of lifting bases of the period in question. Therefore, demanded that markers of knowledge such as Philosophy, History, Theology, Laws and even the Art were rethinking. The event in question generates a reflection on the capacity of History to apprehend phenomenon occurred in the past for a relevant form to the present. Involving theoretical and dynamics questions of the historiographer work, which goes since the way this work is made to its motivations. Between the trauma that shoah evokes and difficulties that it brings to Historiographical field is the important question of the use of History. One battle aiming the administration of history and shoah s memory is in full development, in it is highlighted the Negationists of shoah, group that alleges that the cited event has not occurred. The present work aims to be an analysis of Negationists attempts to administrate the history of shoah, its memory and how they use History, as the authenticity of their work while history. For such fact, some work of main Negationists authors such as Paul Rassinier and Robert Faurisson will be inquired, also other important authors of the group as: Mark Weber, David Irving and Arthur Butz.